Worldwide prevalence of Helicobacter pylori in patients with Mucosa-Associated Lymphoid Tissue (MALT) lymphomas: A systematic review and meta-analysis - Abdelfattah, Ali; Al-Khreisat , Mutaz Jamal; Al-Sanabra , Ola Mohammed; Johan, Muhammad Farid; Hussain , Faezahtul Arbaeyah; Zueter , AbdelRahman M.; Abuyaman , Omar; Jacoub , Khaldun; Omoush , Samya A.; Ismail , Nor Hayati; Yusoff , Abdul Aziz Mohamed; Islam , Md Asiful; et al. (Acta Biomedica Atenei Parmensis, 2026)
Background/Objective: Chronic inflammation resulting from infections or autoimmune disorders plays a pivotal role in the pathogenesis of mucosa-associated lymphoid tissue (MALT) lymphoma, an extranodal non-Hodgkin lymphoma. Helicobacter pylori (H. pylori) is a major contributor to gastric MALT lymphomas. Eradicating H. pylori can induce regression of these lymphomas. However, the global prevalence of H. pylori among MALT lymphoma patients remains insufficiently studied. The present study aimed to determine this global prevalence, crucial for developing effective treatments and improving outcomes. Methods: An electronic search of five databases using appropriate keywords was performed, including PubMed, Scopus, Cochrane, ScienceDirect, and Google Scholar. The quality of the involved manuscripts was evaluated utilizing the Joanna Briggs Institute critical appraisal tool. The random-effects model was used to report the results as percentages with a 95% confidence interval (CI). The protocol was registered with PROSPERO (CRD42024541706). Results: Of the 2524 titles identified, 102 studies met the inclusion criteria. The prevalence of H. pylori in patients with MALT lymphomas was 73.0% (95% CI, 69.0–77.1%, n = 8725). The outcomes of sensitivity analysis were consistent, and 70.6% of studies were deemed high quality. Significant publication bias was found by Egger’s test. Conclusion: H. pylori was found in a significantly high proportion of patients with MALT lymphomas. This study recommends that H. pylori testing and eradication should be considered for prediction, targeted treatment protocols, and assessment of the clinical status of MALT lymphomas.